De l’injonction à l’autonomie à l’impossibilité de l’intimité pour des jeunes filles « handicapées » vivant en institution spécialisée - Léa Anthouard; Julie Thomas (Genre, Sexualité et Société)
This article focuses on the daily life of young girls with disabilities who live in a special education institute. It investigates the tension between the aim of autonomy and the constraining conditions: what does it produce on the practices of the professionals and on the experiences of these young girls, regarding intimacy? The analysis of the 7-month ethnographic fieldwork shows a rather limited definition of autonomy, with no account taken of the question of intimacy. Autonomy is often taken in an everyday sense overhung by a medical conception, as a preparation to acquire practical skills and not as the possibility of exercising the choices governing the conduct of one’s own life. In practice, this objective leads, paradoxically, to putting residents constantly under the gaze of professionals. Residents do not have the time or private space that would allow them to take intimate ownership of their autonomy. Solitary intimacy, a time-space for the formation of autonomous thought, is denied as a choice and a right: it is imposed and a form of punishment in the eyes of the educators.